Improving food safety in Ukraine - Romanenko, Victoria (My University, 2013)
Analysis of factors that affect food safety.
Keywords: health; food industry; safety; охорона здоров'я; продовольча безпека; харчова промисловість; здравоохранение; пищевая промышленность; продовольственная безопасность; кафедра вищої математики імені проф. Можара В. І.